THE INFLUENCE OF ACETATE AND OXALATE AS SIMPLE ORGANIC LIGANDS ON THE BEHAVIOR OF PALLADIUM IN SURFACE ENVIRONMENTS - Wood S.A.; Van Middlesworth J. (My University, 2004)
Acetate and oxalate are simple organic ligands that occur naturally in surface waters, groundwaters, and soils; they may play a role in the transport of palladium in such environments. Mass transfer of Pd in surface environments has implications for geochemical exploration as well as the environmental impact of the platinum-group elements. The complexation of divalent palladium and acetate was studied via measurement of the solubility of amorphous Pd(OH)2 in 1 molal NaClO4 as a function of concentration of acetate (0.0001 to 0.1 molal) at 25°C. From these data, the predominant Pd 2+ acetate species was determined to be Pd(ac)2 0 (where ac denotes the acetate anion), with a conditional stability-constant of log 2 * = 9.3 ± 0.3. Palladium oxalate complexes were investigated using UV-visible spectrophotometry. Experiments were conducted at 25°C as a function of concen- tration of NaCl (0.1 to 2.0 molal) and oxalate (0.1 to 100 millimolal). The results demonstrate that oxalate-bearing Pd species become important at relatively low concentrations of oxalate. At 1 molal NaCl, the existence of an isosbestic point indicates an equilibrium between one oxalate-bearing Pd species and PdCl4 2- . At lower concentrations of NaCl, more than two Pd species may be present under the experimental conditions. Calculation of speciation as a function of pH in a model soil solution shows that Pd(ac)2 0 never exceeds 40% total Pd, even in the absence of oxalate and at acetate concentrations as high as 5 millimolal. At lower concentrations of acetate or in the presence of oxalate, the proportion of Pd(ac)2 0 is negligible. However, Pd(ox) 0 appears to be an important Pd 2+ species, predominating at low pH, with its field of predominance expanding with increasing concentration
Keywords: palladium; acetate; oxalate; organic ligands; solubility; complexation; absorption spectroscopy; environmental geochemistry; exploration geochemistry